UNFAIR TERMS IN A TENANCY AGREEMENT INVOLVING OFF-CAMPUS STUDENTS: A LEGAL DISCUSSION - Farihana Abdul Razak; Nurhidha Irawaty Kasmaruddin; Anuar Kassim (INTERNATIONAL JOURNAL OF LAW, GOVERNMENT AND COMMUNICATION (IJLGC), 2024)
Some universities in Malaysia with a large number of students enrolled every year cannot cope with the increasing demand for students’ accommodation, therefore students have to find rental houses near the university. The purpose of this paper is to explore the unfair terms in a tenancy agreement involving off-campus students and rental house owner. The underlying philosophy is that students who have reached the age of majority and sound mind are free to enter into contracts and must, therefore, understand the legal effects of contract for which they have agreed. This paper gathers data from the tenancy agreement collected by several numbers of students who are staying off-campus at UiTM Perak Branch, Tapah Campus, through references to statutes and case reports to police. Thus, it discussed the legal effects of unfair terms in a tenancy agreement involving off-campus students and this study proposed three recommendation. The first is to educate students on the understanding of the clause in the tenancy agreement and the legal effect for breach of contract, the second is to educate the rental house owners on the importance of fairness clauses for both parties in a tenancy agreement and, thirdly, to recommend the university’s non-resident unit under Students Affairs (HEP) to draw up a sample of win-win tenancy agreements as guidelines for both parties. Hopefully, this paper would contribute to the body of knowledge in the area of law of contract.